SARANA MAKAN UNTUK MENGATUR POLA MAKAN PENDERITA DIABETUS MELITUS - Bagus Ajidani; Markus Hartono; Wyna Herdiana (CALYPTRA, 2018)
Diabetic is one of the deadly diseases and should be watched our for. This disease in Indonesia is one of the most feared amongst others. Those who have it tend to easily get complications in their internal organs which results in faster death.The purpose of this food medium is to help the diabetics control their eating pattern which could improve the quality of their life by not worsening their health condition. From the research, there will be a set of food mediums with the concept "plate and lunch box for diabetics portion". This concept is implemented by adjusting the needs of the diabetics along with the suggestions that could be used in or out side of their home with the right food portion for them. The method used in this research is a combination of a quantitative and qualitative research method. Through the research, it's found that not all those who have diabetes knows how to eat properly based on their health condition when it's really important and crucial to know how. The lack of proper food mediums in Indonesia for the diabetics plays a role in this factor. Thus, there's a need for a proper set of food mediums for the diabetics in order to maintain the right way for them to eat. So With this product can set the diet food’s portion that are appropriate for patients and there is a reminder tool to remind the time for eat and consume the drugs.